Indo-Eroticism in “Las mareas vuelven de noche,” by Yolanda Oreamuno - Camacho Arias, Ariadne (2018)
This study explores Oriental eroticism in “Las mareas vuelven de noche,” by the Costa Rican author Yolanda Oreamuno. This short story narrates an encounter between an oriental woman and an occidental man, addressing the experience of eroticism in India. The text proposes the union of the lovers as a transcendental act. In the narration, eroticism is viewed in different scenes drawn by the senses strengthening the spiritual, divine-like and ethereal atmosphere of coming together in love.